COMMUNITY DEVELOPMENT BADAN EKSEKUTIF MAHASISWA UNIVERSITAS PENDIDIKAN MANDALIKA - Suhardi, Muhamad; Zinnurain, Zinnurain (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2022)
Abstract: This study aims to evaluate the Community Development Program of the Student Executive Board (BEM) of the Mandalika University (UNDIKMA) for the 2021/2022 term of service by using the Kirckpatrick Four Level evaluation model. The Community Development Program of the Student Executive Board (BEM) of the Mandalika Education University (UNDIKMA) in the form of the Community Development program was carried out in Dasan Agung Village, Selaparang District, Mataram City. This program focuses on education, such as a course for students called Smart School which is held every Sunday from 10.00 WITA to 12.00, and recitation for housewives every Tuesday at 13.00 WITA until 15.00 WITA. UNDIKMA students have several obstacles caused by the relocation of residents who take part in this program as a result of the Mataram City government's policy in regulating urban planning. The UNDIKMA Student Executive Board chose to provide consistency to continue the Community Development program by developing a new strategic plan with the aim of creating participant independence and enabling them to improve their standard of living. Keywords: Program Evaluation, Community Development, BEMAbstrak: Penelitian ini bertujuan untuk mengevaluasi program Community Development Badan Eksekutif Mahasiswa (BEM) Universitas Pendidikan Mandalika (UNDIKMA) masa bakti 2021/2022 dengan menggunakan model evaluasi Four Level Kirckpatrick. Program Community Development Badan Eksekutif Mahasiswa (BEM) Universitas Pendidikan Mandalika (UNDIKMA) dalam bentuk program Bina Lingkungan dilaksanakan di Kelurahan Dasan Agung Kecamatan Selaparang Kota Mataram. Program ini fokus pada bidang pendidikan, seperti kursus untuk siswa yang diberi nama Sekolah Cerdas yang diadakan setiap hari Minggu pukul 10.00 WITA hingga pukul 12.00, dan pengajian bagi ibu-ibu rumah tangga pada setiap Selasa pukul 13.00 WITA hingga pukul 15.00 WITA Bina Lingkungan Badan Eksekutif Mahasiswa UNDIKMA memiliki beberapa kendala yang disebabkan oleh relokasi warga yang mengikuti program ini sebagai dampak dari kebijakan pemerintah Kota Mataram dalam mengatur tata kota. Badan Eksekutif Mahasiswa UNDIKMA memilih untuk memberikan konsistensi untuk melanjutkan program Bina Lingkungan dengan menyusun rencana strategis baru dengan tujuan untuk menciptakan kemandirian peserta dan membuat mereka dapat meningkatkan taraf hidup mereka.Kata Kunci: Evaluasi Program, Community Development, BEM